A influência das características tecnológicas, organizacionais e ambientais na adoção do CRM pelas startups - Souza, Érica Wisnheski de (2023)
The growth of the startup market promotes an increase in innovation in products and services, making the market even more modern. To make possible an advance in the technology used by them and acquire more and more investments for their expansion, it is essential to have a Customer Relationship Management (CRM) in order to reach and retain more customers. Therefore, it is important to understand what is necessary for the consumer, what his profile is, and to promote ways to achieve a high performance in the quality of the relationship between him and the startup. To this end, this study has as its general objective to understand the adoption of CRM in Brazilian startups through the framework of Technology, Organization and Environment (TOE). And as specific objectives it seeks to understand what and how technological, organizational and environmental characteristics contribute to the adoption of CRM in Brazilian startups. In relation to the methodological procedures, the research is qualitative in nature, and of the exploratory type. The strategy used is multiple case study carried out in eight startups based on previously established criteria. As a source of evidence, documents and semi-structured interviews with employees who work directly with CRM were used. And for treatment of evidence analysis, the technique adopted was content analysis. The results show that most startups believe to be important in the adoption of CRM the technological characteristics: perceived and relative advantage; compatibility; observability; security; quality and data integration; the organizational characteristics: financial resources and knowledge of employees; the environmental characteristics: competitive and customer pressure. While in the technology characteristic: the trialability and in the organizational characteristic: the top management support did not have so much importance for most of the selected startups regarding the CRM adoption. As a contribution, the insights generated in this dissertation can guide further research on innovation and technology in the context of startups with the use of CRM based on the TOE framework.